Reaching for Returns in Retail Structured Investment - Sonsino, Doron; Lahav, Yaron; Roth, Yefim (Management Science, 2022)
The growing market for retail structured investment products and empirical evidence for excessive pricing of such products raise the hypothesis that private investors show increased risk appetite in structured investment contexts. A two-stage framed field experiment building on cumulative prospect theory is designed to test this hypothesis. Subjects’ expectations regarding the future performance of an underlying index are elicited first. A bisection algorithm is then applied to derive the certainty equivalents of 20 simple individually tailored deposits. The results support the increased risk appetite hypothesis, revealing that subjects reach for substantial gains and underweight tail loss events when evaluating the deposits. Similar results emerge in a follow-up experiment where the uncertain deposits are replaced by risky versions. While previous studies propose that misperception of complex terms and optimism contribute to the mispricing of structured instruments, the current experiments show that nonstandard risk appetite manifests in the valuation of simple well-defined products, controlling for expectations. This paper was accepted by Manel Baucells, decision analysis.